2016
DOI: 10.1021/acs.biochem.5b00945
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Protein Mass Modulation on Human Dihydrofolate Reductase

Abstract: Dihydrofolate reductase (DHFR) from Escherichia coli has long served as a model enzyme with which to elucidate possible links between protein dynamics and the catalyzed reaction. Such physical properties of its human counterpart have not been rigorously studied so far, but recent computer-based simulations suggest that these two DHFRs differ significantly in how closely coupled the protein dynamics and the catalyzed C-H→C hydride transfer step are. To test this prediction, two contemporary probes for studying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
87
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(92 citation statements)
references
References 53 publications
4
87
0
1
Order By: Relevance
“…The observed change in the (intrinsic) KIEs can be achieved in a number of ways besides isotopic labeling of protein and/or cofactor; 33 eg: hydrostatic pressure, 62 site-directed mutagenesis 63,64 and alterations in protein solvation, 65 use of un-natural (alternate) substrates, 66,67 or even species variation across the evolutionary timeline (eg: variation in the intrinsic KIE values of ecDHFR and hsDHFR although both show temperature independence) 28 etc. The interpretation of the temperature dependence of KIEs, however, is similar in all of these instances, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed change in the (intrinsic) KIEs can be achieved in a number of ways besides isotopic labeling of protein and/or cofactor; 33 eg: hydrostatic pressure, 62 site-directed mutagenesis 63,64 and alterations in protein solvation, 65 use of un-natural (alternate) substrates, 66,67 or even species variation across the evolutionary timeline (eg: variation in the intrinsic KIE values of ecDHFR and hsDHFR although both show temperature independence) 28 etc. The interpretation of the temperature dependence of KIEs, however, is similar in all of these instances, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…21,23 It was suggested that these studies reflect a decrease in the frequency of fs motions that are linked to barrier crossing and that the outcomes support the concept of “Born Oppenheimer” enzymes. Studies on bacterial and human dihydrofolate reductase (DHFR) 14,28 revealed no effect of the heavy DHFR on intrinsic KIEs (at physiological temperatures); however, the mass alteration affected protein-ligand interactions, which are expected to take place at a slower timescale, and may indicate alteration of the protein potential surface.…”
Section: Introductionmentioning
confidence: 99%
“…It seems that the experimental studies using KIE int agree well with the first but did not test the second theoretical approach. Additionally, TPS calculatins of the human DHFR (hsDHFR) predicted significant PPVs, but KIE int for both light and heavy hsDHFR where identical throughout the temperature range (Francis, Sapienza, Lee, & Kohen, 2016), falling to support the theoretical prediction. Similarly, in a different TPS study of liver alcohol dehydrogenase, it was predicted that the valine residues at position 203 and 207 facilitate enzyme catalysis as part of the PPV (Caratzoulas, Mincer, & Schwartz, 2002).…”
Section: Computational Vs Experimental Studiesmentioning
confidence: 89%
“…Programmsysteme der klassischen MD, damit sie auf biomolekulare Tunnelprozesse anwendbar sind. 34,[41][42][43][44][45][46][47][48][49][50][51][52] Ein weiteres Verfahren, die Quantendynamik vielatomiger Moleküle zu beschreiben, beruht auf der MCTDH-Methode (Multi Configuration Time Dependent Hartee). [53][54][55][56] Das Multimode-Package wurde ebenfalls auf Tunnelprobleme angewandt.…”
unclassified